Evaluasi Tingkat Kematangan Manajemen Layanan Pemantauan Base Transceiver Station (BTS) Pada Unit Network Monitoring System (NMS) Berdasarkan ITIL V3 Dengan Domain Service Operation Pada Badan Aksesibilitas Telekomunikasi Dan Informasi Kominfo - Selaras Aura Mahardhika; Ismiarta Aknuranda; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Badan Aksesibilitas Telekomunikasi dan Informasi (BAKTI) is a work unit under the auspices of the Ministry of Communication and Information Technology which is tasked to provide wider telecommunications access services, especially in 3T areas, namely Remote, Outermost and Left behind areas. BAKTI has many priority programs, one of programs is the construction of the Base Transceiver Station (BTS) project. After the construction of the BTS is carried out, the performance of BTS device is monitored by using the PRTG application managed by the NMS work unit, while the service users are the BTS component providers. In its implementation, it was found that there were a number of sites that had a difference in the value of avaibility between the values stated in the PRTG BAKTI and the value stated on the PRTG of the component providers. Therefore, this study aims to determine the causes of problem and evaluate service management of the NMS work unit that manages the service. This evaluation uses the ITIL V3 framework that using the Service Operation domain. From the results of the research that has been done, the maturity value obtained is 1.93 or at level 2. From the NMS unit also wants the maturity level to reach a value of 2.76 or at level 3. Therefore, to achieve the desired expectation value, the research resulted in 21 recommendations to improve and fulfill the shortcomings of the NMS BAKTI unit management.